1994
DOI: 10.1002/app.1994.070520917
|View full text |Cite
|
Sign up to set email alerts
|

Copolymers of 1,5‐dioxepan‐2‐one and L‐ or D,L‐dilactide: Hydrolytic degradation behavior

Abstract: SYNOPSISThe degradation of two series of copolymers made of 1,5-dioxepan-2-one (DXO) and Lor D,L-dilactide has been investigated. In uitro degradation of the six copolymers with different ratios of the ingoing components was followed using size exlusion chromatography ( SEC) , nuclear magnetic resonance (NMR) spectrometry, Fourier transform infrared (FTIR) spectroscopy, and differential scanning calorimetry (DSC) . The copolymers with a high content of lactic acid units showed a higher rate of hydrolysis than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…[1][2] We have shown that classical theory of polyester hydrolysis applies to DXO-L-LA copolymers as well. 10 The molecular weight started to decline immediately upon immersion in buffer (Fig. 2).…”
Section: In Vitro Degradation Of Poly(dxo-co-l-la) Microspheresmentioning
confidence: 96%
See 2 more Smart Citations
“…[1][2] We have shown that classical theory of polyester hydrolysis applies to DXO-L-LA copolymers as well. 10 The molecular weight started to decline immediately upon immersion in buffer (Fig. 2).…”
Section: In Vitro Degradation Of Poly(dxo-co-l-la) Microspheresmentioning
confidence: 96%
“…This behavior has been confirmed for DXO-rich amorphous copolymers. 10 L-lactide-rich copolymers, on the other hand, became enriched in lactide units because the crystalline lactide material is more resistant to water penetration and bulk erosion than the amorphous DXO units.…”
Section: In Vitro Degradation Of Poly(dxo-co-l-la) Microspheresmentioning
confidence: 98%
See 1 more Smart Citation
“…Dependiendo del iniciador, la polimerización procederá por tres diferentes mecanismos [45]: el catiónico, el aniónico y el de inserción-coordinación [46][47][48]. Existen otros como el mecanismo radical, zwiteriónico [49] o por hidrógenos activos que no son muy utilizados debido a la obtención de polímeros de muy bajo peso molecular.…”
Section: Rop De Los éSteres Cíclicosunclassified
“…La ROP pseudo-aniónica es a menudo llamada ROP de coordinación-inserción, ya que el proceso de propagación se piensa que procede por la coordinación del monómero con las especies activas, seguida por la inserción del monómero entre el enlace metal-oxígeno por la reorganización de los electrones [46,47]. La figura 1.5 muestra la representación esquemática del mecanismo de coordinación-inserción.…”
Section: Rop De Coordinación-inserciónunclassified